Sexual behavior of women in the process of transexualization in front of safe sex: Integrative review (Research, Society and Development, 2021)
Objective: To analyze the scientific evidence related to the sexual behavior of women undergoing transsexualization in the face of safe sex. Method: Integrative literature review, carried out in the PUBMED, Web of Science, Lilacs, Scopus and CINAHL databases, to answer the guiding question: What are the sexual behaviors of women undergoing transsexualization in relation to safe sex found in the scientific literature? The searches took place between August and November 2020, using the descriptors “transsexuality / transsexualism”; “Women / woman”; “Sexual behavior / sexual behavior”; “Safe sex” and “sexual health / sexual health”. After searching with the intersections of these descriptors, 2,915 articles were identified. When applying the eligibility criteria, ten studies were selected, assessed for methodological rigor and level of evidence. In extracting the data, a validated and adapted instrument was used. Results: Among all the safe sex strategies identified in the studies, the prevention of Sexually Transmitted Infections - STIs through health education actions were the most significant in the context of the sexual behavior of trans women. Conclusion: This research made it possible to understand that trans women recognize the importance of safe sex, but often have behaviors that put their sexual health at risk. The factors associated with the low adherence to safe sex for these women are related to the fragility of the socio-cultural, educational and health sector.